2008
DOI: 10.1179/174328408x302558
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetic field induced strain in ferromagnetic shape memory alloys and its condition

Abstract: Ferromagnetic shape memory alloys are a kind of multiferroic material, in which a ferroelastic domain (variant in the martensite phase) and a magnetic domain are closely correlated. One interesting phenomenon due to this correlation is the rearrangement of variants by a magnetic field, which causes a large magnetic field induced strain of several percent. Typical alloys exhibiting such behaviour are disordered Fe–31˙2Pd, Fe3Pt (degree of order ∼0˙8) and Ni2MnGa. In the present paper, the martensitic transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…The occurrence of giant reversible magnetic deformation in a magnetic field observed in these alloys is due to the rearrangement of twin martensitic variants under the action of an external magnetic field due to the strong magnetocrystalline anisotropy and high mobility of twin boundaries. Similar properties are also observed in alloys such as Ni2MnAl, Co2MnGa, Co2MnAl [159], Fe-Pd [160], Fe-Pt [161], Co-Ni-Ga [162], Co-Ni-Al [163], and some others.…”
Section: Smart Fillerssupporting
confidence: 71%
“…The occurrence of giant reversible magnetic deformation in a magnetic field observed in these alloys is due to the rearrangement of twin martensitic variants under the action of an external magnetic field due to the strong magnetocrystalline anisotropy and high mobility of twin boundaries. Similar properties are also observed in alloys such as Ni2MnAl, Co2MnGa, Co2MnAl [159], Fe-Pd [160], Fe-Pt [161], Co-Ni-Ga [162], Co-Ni-Al [163], and some others.…”
Section: Smart Fillerssupporting
confidence: 71%
“…はパラメータである.導出の詳細は原著論文 (18) を参考して いただきたい.また,この式を考慮すると,TTT 曲線にお 合金の TTT 図 (26) (30) . 図11 Fe 3 Pt における電子状態密度(DOS)の軸比(c/a) 依存性 (32) .フェルミエネルギー E F 直下にある ピークが正方晶ひずみを与えることにより 2 つ に分離することで,系のエネルギーを低下させ ている. 図12 Fe 31.2Pd(at)合金 (34) ならびに Fe 3 Pt (35) にお ける応力 ひずみ曲線の温度依存性. ( 1 ) 西山善次マルテンサイト変態基本編,丸善,(1972).…”
Section:  は じ め にunclassified
“…It is now well understood that magnetocrystalline anisotropy, twinning shear and twinning stress are important factors for realizing the rearrangement of variants. 5) Similar selection of variants was also found in an Fe-Pd alloy exhibiting a disorder-order transformation from the A1-type structure to the L1 0 -type structure by Oshima et al 6) and Tanaka et al 7) We also reported that a single variant of the ordered phase can be obtained in Co-50Pt 8) and Fe-55Pd 9) alloys by making two-step ordering heat-treatments: the first step was made under a magnetic field, and the second step was made under no magnetic field.…”
Section: Introductionmentioning
confidence: 99%